REGULASI KESELAMATAN PASIEN DI RUMAH SAKIT DI DAERAH ISTIMEWA YOGYAKARTA - , MARIA YOSEPHA ASIHSUTANTRI, Prof. dr. Adi Utarini, MSc., MPH, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Even after a decade, the application of patient safety is still varied, yet not many successes have been achieved and there are still some obstacles although many parties potentially act as facilitators. External environment such as external regulatory is thought to be one factor that could encourage the implementation of patient safety in hospitals. Objective: To identify the external regulation of patient safety